Early and late results of surgical treatment of multifocal epilepsy - V. R. Kasumov (Бюллетень сибирской медицины, 2009)
Studies of surgical outcomes in multifocal epilepsy patients showed them to depend on epileptic foci sites in two groups of the diseased according to J. Engel scale (1993): 92 early postoperative period patients (group 1), and 30 late one patients (group 2). Of 92 group 1 patients unilateral cortical epileptic foci were diagnosed in 62 (51.7%), bitemporal ones in 30 (20.0%) patients. Of 30 group 2 patients – unilateral cortical in 17 (42.5%), and bitemporal in 13 (32.5%) patients. In group 1 remission of the seizures and decrease of their frequency over 80.0% was achieved in 80.4% of the patients, in group 2 – decrease of seizure frequency over 50.0% in 67.7%, and recurrent seizures in 26.7% of the patients.